Incremental Linear Programming Optimal Power Flow: Including the VAR Cost Function (University of Khartoum Engineering Journal, 2022)
In this paper, the full AC incremental linear programming optimal power flow using POWERWORLD® Simulator and Microsoft® Excel is presented. A proposed formulation of including the VAR cost function to the objective function and an implementation of the proposed formulation in a 6-bus test system and the IEEE 30 bus system was made in order to decide whether this formulation favorably or unfavorably affects the optimization process. Research proved that this formulation can improve the total optimization process but not for all system types and sizes; the effect was favorable for the 30-bus system and unfavorable for the 6-bus system.